A theoretical study of acrylonitrile adsorption on Si(001) - León-Pérez, F. de (2004)
The present work is a comparative study of possible adsorption structures of the conjugated molecule acrylonitrile on Si(001) employing the state of the art pseudopotential method, within a generalized gradient approximation to the density functional theory. In the recent literature it is proposed the interaction of acrylonitrile with Si(001) through a cycloaddition reaction of the cyano group, in competition with the bounding of the two outer atoms of the molecule skeleton with the Si dimer in cross-dimer and cross-trench geometries; between other geometries like which correspond the reaction of the C = C bond with a Si dimer. Starting from a large number of configurations our calculations favor the planar cycloaddition through the terminal N and C atoms on the Si dimer. In this way we explain the electronic and vibrational features obtained experimentally.